Mediation of Brand Equity in The Influence of Integrated Marketing Communication on Purchase Intention of Mie Gacoan Restaurant in Yogyakarta - Mahendra Putri, Windi; Sutiono, Heru Tri; Kusmantini, Titik (Manajemen FEB Unima, 2024)
This study aims to determine the effect of Integrated Marketing Communication (IMC) on Purchasing Intention at Gacoan noodle restaurants mediated by Brand Equity. The method in this study uses Partial Least Squares (PLS) using SmartPLS 3. The population in this study were Gacoan Noodle Customers in Gajayan Yogyakarta with the sampling technique used, namely purposive sampling, and obtained a research sample of 100 samples. For the feasibility of the model using GoF, the results show that the feasibility value is 0.51 and can be said to be high. For the relationship between variables directly, IMC has a significant positive effect on Purchasing Intention and Brand equity has a significant positive effect on Purchasing Intention. For the relationship between variables indirectly, the results show that Integrated Marketing Communication (IMC) has a significant positive effect on Purchasing Intention which is mediated by Brand Equity.